Better than a pound of cure: preventing the development of multidrug-resistant tuberculosis. (9th March 2018) - Byrne, Anthony L; Fox, Greg J; Marais, Ben J
Diagnostic and treatment delays contribute to increased death and disability among the 490, 000 adults and children who develop multidrug-resistant (MDR) tuberculosis every year. Since the treatment of MDR tuberculosis is complex, costly and often toxic, tuberculosis control programs should prioritize strategies to prevent drug-resistant tuberculosis. Opportunities to limit transmission and prevent disease progression in close contacts of MDR tuberculosis cases are often neglected. Effective MDR tuberculosis preventive strategies could minimize the costs for patients and healthcare systems. This review characterizes the biological basis for the development of MDR tuberculosis, outlines the evidence for strategies to reduce transmission and highlights programmatic approaches to the management of patients infected with drug-resistant strains of Mycobacterium tuberculosis .